EVALUASI PELAKSANAAN GOOD MANUFACTURING PRACTICES(GMP) DAN ANALISIS EFISIENSI BIAYA DI PUSAT PENGOLAHAN KAKAO RAKYAT JEMBRANA BALI - Tidar Aden Hawa (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2017)
Although the amount of Indonesian cocoa production is quite high, but the volume of cocoagrinding is still relatively low compared to the potential that should be obtained. Therefore, Indonesia should improve the cocoa processing industry sector.This research was intended to: analyze the implementation of each component of Good Manufacturing Practices (GMP) at Smallholder Cocoa Processing Center (PPKR) of Jembrana in accordance with Agriculture Minister’s Regulation No. 35/Permentan/OT.140/7/2008; analyze the efficiency level of the use of costs at PPKR Jembrana. The research results showed that the level of GMP implementation based on Agriculture Minister’s Regulation No.35/Permentan/OT.140/7/2008 at PPKR Jembrana was still partial (47%). In the one year production, the use of costs at PPKR Jembrana was efficient indicated by the value of R/C>1, but the value was resulted by subsidized cost structure (cost of raw materials/cocoa seeds, employee salaries, depreciation of equipment, machinery depreciation, building depreciation, property and building taxes, electricity cost, and water cost). If subsidies were removed, the value of efficiency would drop even become inefficient. By the whole implementation of GMP, the inefficient costs in form of process failure cost and product return cost can be reduced, so the efficiency of the costs use will increase.